Social innovation using the example of consortia of social economy entities - Błażejowska, Małgorzata (Społeczne innowacje na przykładzie konsorcjów podmiotów ekonomii, 2020)
The aim of the article is to present the functioning of consortia composed of various legal forms of social economy entities. The subject of the research are consortia operating under the brands: “Klunkry”, “Panato Bag” and “Juchowo Farm”. They include social cooperatives, establishments of professional activity, foundations, associations, social integration centrers and non-profit companies. The mutual cooperation of various legal forms of social economy entities, an innovative management mechanism, and manufactured products are an example of social innovations. Based on the data from the National Court Register, the activity profile, employment level, period of operation, founding entities and the financial situation of the analysed units were examined using the dynamics index method. The research results show that working together is beneficial both financially and socially. All the surveyed entities achieved an increase in revenue compared to the previous year. Thanks to the initiatives, socially excluded people found support and employment.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2020; vol. 64, nr 9, s. 5-15
Keywords: consortia; social economy entities; social innovations